Dietary influences on the Dahl SS rat gut microbiota and its effects on salt‐sensitive hypertension and renal damage. (26th April 2021) - Abais‐Battad, Justine M.; Saravia, Fatima L.; Lund, Hayley; Dasinger, John Henry; Fehrenbach, Daniel J.; Alsheikh, Ammar J.; Zemaj, Jeylan; Kirby, John R.; Mattson, David L.
Abstract: Aim: Our previous studies have demonstrated the importance of dietary factors in the determination of hypertension in Dahl salt‐sensitive (SS) rats. Since the gut microbiota has been implicated in chronic diseases like hypertension, we hypothesized that dietary alterations shift the microbiota to mediate the development of salt‐sensitive hypertension and renal disease. Methods: This study utilized SS rats from the Medical College of Wisconsin (SS/MCW) maintained on a purified, casein‐based diet (0.4% NaCl AIN‐76A, Dyets) and from Charles River Laboratories (SS/CRL) fed a whole grain diet (0.75% NaCl 5L79, LabDiet). Faecal 16S rDNA sequencing was used to phenotype the gut microbiota. Directly examining the contribution of the gut microbiota, SS/CRL rats were administered faecal microbiota transfer (FMT) experiments with either SS/MCW stool or vehicle (Vehl) in conjunction with the HS AIN‐76A diet. Results: SS/MCW rats exhibit renal damage and inflammation when fed high salt (HS, 4.0% NaCl AIN‐76A), which is significantly attenuated in SS/CRL. Gut microbiota phenotyping revealed distinct profiles that correlate with disease severity. SS/MCW FMT worsened the SS/CRL response to HS, evidenced by increased albuminuria (67.4 ± 6.9 vs 113.7 ± 25.0 mg/day, Vehl vs FMT, P  = .007), systolic arterial pressure (158.6 ± 5.8 vs 177.8 ± 8.9 mmHg, Vehl vs FMT, P  = .09) and renal T‐cell infiltration (1.9‐fold). Amplicon sequence variant (ASV)‐based analysis of faecal 16S rDNA sequencing data revealed taxa that significantly shifted with FMT: Erysipelotrichaceae_2, Parabacteroides gordonii, Streptococcus alactolyticus, Bacteroidales_1, Desulfovibrionaceae_2, Ruminococcus albus . Conclusions: These data demonstrate that dietary modulation of the gut microbiota directly contributes to the development of Dahl SS hypertension and renal injury.